2019
DOI: 10.3389/fnint.2019.00007
|View full text |Cite
|
Sign up to set email alerts
|

Mental Rotation of Digitally-Rendered Haptic Objects

Abstract: Sensory substitution is an effective means to rehabilitate many visual functions after visual impairment or blindness. Tactile information, for example, is particularly useful for functions such as reading, mental rotation, shape recognition, or exploration of space. Extant haptic technologies typically rely on real physical objects or pneumatically driven renderings and thus provide a limited library of stimuli to users. New developments in digital haptic technologies now make it possible to actively simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 88 publications
2
14
0
Order By: Relevance
“…Critically, these letters could be rotated at four angles (0 • , 90 • , 180 • , 270 • ), thus obligating participants to engage in mental rotation of the presented stimuli. (Tivadar et al, 2019) results support the fact that participants successfully managed to build mental representations of these digitallypresented haptic letters, that they were then able to rotate so as to correctly determine the form. It has also been shown that mental rotation in the visually-impaired can be supported by tactile stimuli (see Prather and Sathian, 2002, for a review).…”
Section: Introductionsupporting
confidence: 66%
See 4 more Smart Citations
“…Critically, these letters could be rotated at four angles (0 • , 90 • , 180 • , 270 • ), thus obligating participants to engage in mental rotation of the presented stimuli. (Tivadar et al, 2019) results support the fact that participants successfully managed to build mental representations of these digitallypresented haptic letters, that they were then able to rotate so as to correctly determine the form. It has also been shown that mental rotation in the visually-impaired can be supported by tactile stimuli (see Prather and Sathian, 2002, for a review).…”
Section: Introductionsupporting
confidence: 66%
“…If so, this would mean that participants are able to use digital haptic information to create mental images of 2-D objects, such as letters. Specifically, we expected to see this effect for normal trained as well as new stimuli, contrary to results in sighted (Tivadar et al, 2019), where sighted participants did not perform well with untrained (new) letters. We expect this given higher tactual expertise of visually-impaired and blind participants (Goldreich and Kanics, 2003;Legge et al, 2008;Wong et al, 2011).…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations